Beach morphodynamic and sediment characteristic along Teluk Chempedak to Kuala Pahang - Mustapa, Mohd Zaini; Saad, Shahbudin; Abdul Hadi, Muhammad Salihi; Yunus, Kamaruzzaman (2013)
The dynamic of sandy coastal profile of Pahang during post-monsoon season was studied in order to describe its morphological evolution. A series of surveys together with samples collection were carried out for determining the modification evolved and sediment constituent of the study area. Several location were selected comprising 12 different station comprehended from Teluk Chempedak to Kuala Pahang. The stations were established at random intervals taking into account the morphological factors such as headland and estuary. Samplings and data collection were conducted monthly for I-year period from February 2012 to February 2013. Topographic beach profile data shows no drastic changes at the dune and high-tide area. However, alternate process of deposition and erosion took place at most stations that could be noticed at the mid-tide level and some extent of low-tide area. The monsoon activity has transported the sediment away from the stations causing most stations experienced erosion during monsoon and post-monsoon season. Sediment analyses postulate that sediment size dominated by medium sand classes to fine sand classes where most of the sediments are consists of quartz sand.